Novel on-demand bioadhesion to soft tissue in wet environments - Steele, Terry W. J. (2014)
Current methods of tissue fixation rely on mechanical-related technologies developed from the clothing and carpentry industries. Herein, a novel bioadhesive method that allows tuneable adhesion and is also applicable to biodegradable polyester substrates is described. Diazirine is the key functional group that allows strong soft tissue crosslinking and on-demand adhesion based on a free radical mechanism. Plasma post-irradiation grafting makes it possible to graft diazirine onto PLGA substrates. When the diazirine-PLGA films, placed on wetted ex vivo swine aortas, are activated with low intensity UV light, lap shear strength of up to 450 ± 50 mN cm−2 is observed, which is one order of magnitude higher than hydrogel bioadhesives placed on similar soft tissues. The diazirine-modified PLGA thin films could be added on top of previously developed technologies for minimally invasive surgeries. The present work is focused on the chemistry, grafting, and lap shear strength of the alkyl diazirine-modified PLGA bioadhesive films.